Tridirectional phase-contrast magnetic resonance velocity mapping depicts severe hemodynamic alterations in a patient with aortic dissection type Stanford B - Müller-Eschner, Matthias; Rengier, Fabian; Partovi, Sasan; Unterhinninghofen, Roland; Böckler, Dittmar; Ley, Sebastian; Tengg-Kobligk, Hendrik von (Journal of vascular surgery, 2011)
This report describes flow patterns derived by three-dimensional (3D) three-directional velocity-encoded cine (VEC) magnetic resonance imaging (MRI), in a patient with chronic Stanford type B aortic dissection. Acquired 3D VEC MRI data illustrated an acceleration of blood flow through the primary entry toward the vessel wall of the false lumen, leading to disturbed intraluminal flow. Furthermore, accelerated blood flow was observed in the partially compressed true lumen. 3D VEC MRI data may be helpful to guide physicians for a more comprehensive preoperative and postoperative assessment of complex aortic pathologies.
Gesehen am 15.09.2022